Mothers' experiences of acute perinatal mental health services in England and Wales: a qualitative analysis. (4th March 2022) - Powell, Claire; Bedi, Simran; Nath, Selina; Potts, Laura; Trevillion, Kylee; Howard, Louise
ABSTRACT: Background/Objective: Perinatal mental health services are a current NHS priority and services are being increased for women. There is limited research on mothers' perspectives of these services and most research focuses on mother and baby units (MBUs). This study explored women's views of their experiences of generic wards, MBUs and crisis resolution teams. Methods: A qualitative thematic analysis was conducted on written feedback on a service-user-designed questionnaire. One hundred and thirty-nine women recruited across 42 mental health trusts made comments. Results: Two key themes were identified: support networks and staff authority. Support networks included subthemes relating to families, peers and staff. The theme of staff authority incorporated subthemes about communication, confidence in staff and service-user autonomy. All themes contributed to whether mothers felt safe in these services. Mothers reported the benefits of positive, non-coercive relationships with family and staff for their recovery. The findings highlight that the challenges women face in perinatal settings reflect the literature on general psychiatric services, particularly around coercion. Conclusions: Specific implications for mothers accessing perinatal mental health services: 1) integrated mental health care and support with babies; 2) support with separation from babies for mothers in acute wards; 3) improvement of women's relationships with social services across all services.